2020
DOI: 10.4081/dr.2020.8774
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of body dysmorphic disorder among young social media users: A cross-sectional study

Abstract: Social media that is heavily used in Saudi Arabia has been linked to a negative impact on body image satisfaction. The objective of the current study was to examine the burden, determinants, and impacts of Body Dysmorphic Disorder (BDD) among a community sample of social media users in Saudi Arabia. The Internet-based cross-sectional study was conducted among social media users during January and February 2020. BDD was assessed using a validated BDD Questionnaire. A total of 1010 participants were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 24 publications
5
38
2
2
Order By: Relevance
“…The proportions of students at risk of having BDD was almost similar to previous studies which reported 0.6–12.3% of their male cohort having BDD ( 4 11 ). Once again, the application of different assessment tools to determine BDD in different studies could have resulted in the large range of prevalence observed.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The proportions of students at risk of having BDD was almost similar to previous studies which reported 0.6–12.3% of their male cohort having BDD ( 4 11 ). Once again, the application of different assessment tools to determine BDD in different studies could have resulted in the large range of prevalence observed.…”
Section: Discussionsupporting
confidence: 87%
“…Once again, the application of different assessment tools to determine BDD in different studies could have resulted in the large range of prevalence observed. Most of the respondents in our study were dissatisfied with their whole body and face whereas respondent from other studies were more concern with their hair, face, weight and skin ( 4 , 7 9 , 25 ). Separately, there is a significant association between staying alone and BDD, as individuals with BDD often have poor psychosocial functioning and avoids social interaction ( 26 ).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…A systematic review conducted in 2016 showed that the estimated prevalence of BDD in the general population is around 1.9-2.2% [5]. Locally in Saudi Arabia, the reported prevalence of BDD among the general population is around 4.2-8.8%, and among female students is 4.4-12.3% [6][7][8][9]. Since there is no available up-to-date data concerning the BDD prevalence in Makkah City, Saudi Arabia, to address this, the current study explores the prevalence of body dysmorphic disorder among the general population in Makkah City, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%